Benefits of 25 Years of School District-University Partnerships to Improve Teacher Preparation and Advance School Renewal - Michael C. Holen; Dan C. Yunk (Educational Considerations, 2014)
Generalizing about school district-teacher education program relationships across the long history and broad landscape of teacher preparation in America can prove challenging.
Keywords: Partnerships; teacher; preparation; Advance School Renewal; school-district; University; education; benefits